Beispiel Nr: 08
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 2 x +3 + -4 z=16\\ 4 x +9 y + -1 z=58\\ 1 x +6 y + 2 z=34\\ \\ \\ \textbf{Rechnung:} \\ 2 x + 3 y + -4 z=16\\ 4 x +9 y -1 z=58\\ 1 x +6 y +2 z=34\\ D_h=\left|\begin{array}{ccc} 2\ & 3 & -4\\ 4&9 & -1\\ 1& 6 & 2 \\ \end{array}\right| \begin{array}{cc} 2\ & 3 \\ 4&9 \\ 1& 6 \end{array} \\ D_h=2 \cdot 9 \cdot 2+3 \cdot \left(-1\right) \cdot 1 +\left(-4\right) \cdot 4 \cdot 6 - \left(-4\right) \cdot 9 \cdot 1 -2 \cdot \left(-1\right) \cdot 6 -3 \cdot 4 \cdot 2=-39 \\ D_x=\left|\begin{array}{ccc} 16\ & 3 & -4\\ 58&9 & -1\\ 34& 6 & 2 \\ \end{array}\right| \begin{array}{cc} 16\ & 3 \\ 58&9 \\ 34& 6 \end{array} \\ D_x=16 \cdot 9 \cdot 2+ 3 \cdot \left(-1\right) \cdot 34 +\left(-4\right) \cdot 58 \cdot 6 - \left(-4\right) \cdot 9 \cdot 34 - 16 \cdot \left(-1\right) \cdot 6 -3 \cdot 58 \cdot 2=-234\\ D_y=\left|\begin{array}{ccc} 2\ & 16 & -4\\ 4&58 & -1\\ 1& 34 & 2 \\ \end{array}\right| \begin{array}{cc} 2\ & 16 \\ 4&58 \\ 1& 34 \end{array} \\ D_y=2 \cdot 58 \cdot 2+16 \cdot \left(-1\right) \cdot 1 +\left(-4\right) \cdot 4 \cdot 34 - \left(-4\right) \cdot 58 \cdot 1 -2 \cdot \left(-1\right) \cdot 34 -16 \cdot 4 \cdot 2=-156 \\ D_z=\left|\begin{array}{ccc} 2\ & 3 & 16\\ 4&9 & 58\\ 1& 6 & 34 \\ \end{array}\right| \begin{array}{cc} 2\ & 3 \\ 4&9 \\ 1& 6 \end{array} \\ D_z=2 \cdot 9 \cdot 34+3 \cdot 58 \cdot 1 +16 \cdot 4 \cdot 6 - 16 \cdot 9 \cdot 1 -2 \cdot 58 \cdot 6 -3 \cdot 4 \cdot 34=-78\\ x=\frac{-234}{-39} \\ x=6 \\ y=\frac{-156}{-39} \\ y=4 \\ z=\frac{-78}{-39} \\ z=2\\ L=\{6/4/2\} $